China and the Middle East: Strengthening Relations and Regional Stability - Atiqa Tariq (CISS Insight Journal, 2024)
The Saudi-Iran normalization agreement, brokered by Beijing in March 2023, underscores China’s growing involvement in the political and security landscape of the Middle East. This engagement encompasses a comprehensive array of economic, technological, and geopolitical factors, considering the geostrategic significance of the Middle East. This paper maps the Chinese influence in the Middle East, its implications for global geopolitics, and its effects on regional development. It also assesses the impact of evolving China-Middle East relations on the American military, economic, and political footprint in the Middle East.